The Unsustainability of Economic Man (Ökologisches Wirtschaften - Fachzeitschrift, 2013)
Modern economics is not sufficiently accounting for the work women do or the damage done to the environment. To account for this, economics should focus on social and ecological wellbeing. But what would a sustainable, sufficiency economy look like?